Pengaktifan otak akibat gerakan jari bagi subjek dominan tangan kanan dan kiri - Ahmad Nazlim Yusoff; Mohd Harith Hashim; Mohd Mahadir Ayob; Iskandar Kassim (penerbit ukm, 2006)
Baseline functional magnetic resonance imaging (fMRI) study has been carried out on 2 healthy male subjects with right- and left-hand dominance. The study used the movement of the right- and left-hand fingers to stimulate neuronal activity in the cerebral cortices. The subject was instructed to repeatedly press his fingers against the thumb during the fMRI scans. A five-cycle active-rest paradigm was used with each cycle consists of one active block and one rest block with 10 series of measurements for each block. One hundred fMRI image volumes for each subject were analysed using MatLab and SPM2 software packages. The general linear model (GLM) was employed to statistically estimate the parameters characterising the hemodynamic response model for finger movement. Inferences about the observed brain activations were statistically generated on the basis of Gaussian random field theory (RFT). The results show that, the activated brain regions due to finger movements are located in the precentral gyrus covering the primary motor area. Brain activations are contralateral to the right and left hand finger movements. The active-state signal intensity was found to be significantly (p < 0.001) higher than that of the resting-state. The number of activated voxels were found to be higher in the brain hemisphere controlling the movement of the fingers of the sub-dominant hand for both subjects. The results support the fact that the activated motor area on the brain hemisphere during the movement of the sub-dominant hand experienced a higher hemodynamic response and a larger activated area as compared to the activated regions on the brain hemisphere controlling the finger movement of the dominant hand.